2016
DOI: 10.5606/kbbihtisas.2016.37541
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in far advanced otosclerosis: series of four cases

Abstract: ÖZBu yazıda aşırı ilerlemiş otoskleroz nedeniyle koklear implantasyon uygulanan dört hasta sunuldu. Ameliyat öncesi değerlendirmeler, ameliyat sırasındaki bulgular, komplikasyonlar ve ameliyat sonrası faydalar incelendi. Koklear implantasyon aşırı ilerlemiş otosklerozlu hastaların rehabilitasyonunda mükemmel işitsel sonuçlar sunan bir tedavi seçeneğidir. Fakat koklaer implantasyon sonrası fasiyal sinir uyarımı otosklerozlu hastalarda daha sık görülmektedir. Ayrıca, otosklerozlu hastalarda koklear ossifikasyon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Thirty-eight studies had details of preimplantation imaging involving at least 289 patients (2,5,8,9,17,20–53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-eight studies had details of preimplantation imaging involving at least 289 patients (2,5,8,9,17,20–53).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-six studies reported intraoperative adverse events/surgical approach details involving a minimum of 432 patients (2,5,8,9,14,17,19–33,36–61). Scala tympani/round window ossification was noted in at least 84 patients, and further drilling/resection was reported in at least 48 patients.…”
Section: Resultsmentioning
confidence: 99%